A Review on COVID-19 and Current Repurposing Treatment Strategy - Ahalya S P; Priyadharshini A; Dhivya D; Nila G (Indian Journal of Forensic Medicine & Toxicology, 2021)
A recent outbreak was caused by SARS-CoV-2 was named Coronavirus disease- COVID-19. The first casewas detected in China. It continued to spread globally and later was declared as a pandemic by WHO.Pneumonia like symptoms was observed which later led to respiratory illness, renal impairment, and death.Closed contact, respiratory droplets through cough, and sneeze are the mode transmission. Symptomsgenerally occur 2-14 days after infection. PCR is performed using various samples collected from infectedpatients and is the standard method of diagnosis. Chest X-ray, CT, and the symptoms observed generallyshow the extent of progress of the disease. Although there is no effective cure, currently symptomatictreatment and supportive care are available to reduce pneumonia-like symptoms and to decrease the severityof the condition. Preventive measures proposed by the WHO is to maintain proper personal hygiene, socialdistancing, and the use of the mask.